Penerapan CRM Sebagai Upaya Meningkatkan Kepuasan dan Loyalitas Pelanggan Pada Arya Wedding Decoration - Nur Ayu Lestari Arya; Irianto Irianto; Andrinata Andrinata (LPPM STMIK Royal Kisaran, 2022)
Abstract: Arya Wedding Decoration Sei Alim Ulu Village is a work that is engaged in services that lead to organizing an event or event, which can make it easier for customers or clients who order an event package to Arya Wedding Decoration to be held professionally with maximum results than done by the client. Arya Wedding Decoration in its implementation in organizing events consists of a team in the success of an event. The Arya Wedding Decoration Sei Alim Ulu Village in its implementation experienced several problems, namely the limited promotional media, namely only using social media applications, as well as the limited efforts to retain clients and find new clients in order to increase the existence of the Arya Wedding Decoration Sei Alim Ulu Village party. The problems that have been described underlie the need for a very popular technology whose presence has various features to know client opinions, event package promos, package ratings, event package testimonials, package orders and the convenience of contacting the Makeup and Decoration party because it is supported by an application that is directly connected to the Arya Wedding Decoration Sei Alim Ulu Village via live chat. Keywords: CRM, wedding organizer, PHP and MySQL Abstrak: Arya Wedding Decoration Desa Sei Alim Ulu merupakan pekerjaan yang bergerak dibidang jasa yang mengarah kepada mengorganisasikan suatu kegiatan acara atau event, yang dapat memudahkan pelanggan atau klien yang memesan sebuah paket event ke pihak Arya Wedding Decoration guna diselenggarakan secara professional dengan hasil yang lebih maksimal dari pada dikerjakan sendiri oleh klien. Pihak Arya Wedding Decoration pada implementasinya dalam menyelenggarakan event terdiri dari sebuah tim dalam menyukseskan sebuah event. Pihak Arya Wedding Decoration Desa Sei Alim Ulu dalam implementasinya mengalami beberapa permasalahan yaitu terbatasnya media promosi yaitu hanya menggunakan aplikasi sosial media, serta terbatasnya usaha mempertahankan klien dan mencari klien baru guna meningkatkan eksistensi dari pihak Arya Wedding Decoration Desa Sei Alim Ulu. Permasalahan yang telah diuraikan, mendasari perlunya teknologi yang sangat popular kehadirannya yang memiliki beragam fitur mengetahui pendapat klien, promo paket event, rating paket, testimoni paket event, pemesanan paket dan kemudahan menghubungi pihak Tata Rias dan Dekorasi karena sudah didukung dengan aplikasi yang langsung terhubung dengan pihak Arya Wedding Decoration Desa Sei Alim Ulu melalui live chat. Kata kunci: CRM, wedding organizer, PHP dan MySQL.